Investigation on the simultaneous loss of saccharides in pre-hydrolysis liquor during an efficiently combined process towards lignin removal. (15th November 2022) - Hou, Minjie; Wang, Leiming; Sun, Yanning; Guo, Yanzhu; Sheng, Xueru; Zhang, Fengshan; Sun, Haidong; Fatehi, Pedram; Shi, Haiqiang
Abstract: Generally, lignin separation from prehydrolysis liquor (PHL) is accompanied by sugar removal, making the purification of PHL challenging. However, how sugar loss from PHL can be minimized in PHL purification is still unclear. In this work, a method for removing lignin from PHL was attested, which included treatments of PHL with poly aluminum chloride (PAC), activated carbon, and XAD-4 resin. The results exhibited that the PAC could form complexation with lignin facilitating lignin removal from PHL. At the PAC concentration of 15 mg/L, 10% of lignin was removed, while no significant sugar loss was observed. Subsequently, by treating PHL with activated carbon, 87% of the remaining lignin was removed from the PHL, while sugar loss was identified to be 14%. XAD-4 resin treatment could slightly improve the lignin removal from 87% to 92%. However, the XAD-4 was unselective in sugar removal and led to an increased sugar loss (from 14% to 37%). Interestingly, removing colloidal lignin by PAC benefited the subsequent activated carbon process for improving lignin removal. In other words, PAC removed not only colloidal lignin but also facilities lignin isolation (i.e., an increase from 81% to 87%) and prohibited sugar loss (a drop from 27% to 6%) in the subsequent activated carbon treatment.